Soils and Fertilizers for Master Gardeners: The Soil Profile and Soil Classification - Amy L. Shober (EDIS)
SL-260, a 3-page illustrated fact sheet by Amy L. Shober, provides information about the characteristics and classification of soils as found in the landscape under natural conditions. It is part of a series entitled Soils and Fertilizers for Master Gardeners. Includes references. Published by the UF Department of Soil and Water Science, June 2008.